Recording of Electrically Evoked Neural Activity and Bladder Pressure Responses in Awake Rats Chronically Implanted With a Pelvic Nerve Array - Payne, Sophie C.; Wiedmann, Nicole M.; Eiber, Calvin D.; Wong, Agnes W.; Senn, Philipp; Osborne, Peregrine B.; Keast, Janet R.; Fallon, James B. (Frontiers in Neuroscience, 2020)
Bioelectronic medical devices are well established and widely used in the treatment of urological dysfunction. Approved targets include the sacral S3 spinal root and posterior tibial nerve, but an alternate target is the group of pelvic splanchnic nerves, as these contain sacral visceral sensory and autonomic motor pathways that coordinate storage and voiding functions of the bladder. Here, we developed a device suitable for long-term use in an awake rat model to study electrical neuromodulation of the pelvic nerve (homolog of the human pelvic splanchnic nerves). In male Sprague-Dawley rats, custom planar four-electrode arrays were implanted over the distal end of the pelvic nerve, close to the major pelvic ganglion. Electrically evoked compound action potentials (ECAPs) were reliably detected under anesthesia and in chronically implanted, awake rats up to 8 weeks post-surgery. ECAP waveforms showed three peaks, with latencies that suggested electrical stimulation activated several subpopulations of myelinated A-fiber and unmyelinated C-fiber axons. Chronic implantation of the array did not impact on voiding evoked in awake rats by continuous cystometry, where void parameters were comparable to those published in naïve rats. Electrical stimulation with chronically implanted arrays also induced two classes of bladder pressure responses detected by continuous flow cystometry in awake rats: voiding contractions and non-voiding contractions. No evidence of tissue pathology produced by chronically implanted arrays was detected by immunohistochemical visualization of markers for neuronal injury or noxious spinal cord activation. These results demonstrate a rat pelvic nerve electrode array that can be used for preclinical development of closed loop neuromodulation devices targeting the pelvic nerve as a therapy for neuro-urological dysfunction.